MOFs and their grafted analogues: regioselective epoxide ring-opening with Zr6 nodes. Issue 17 (4th August 2016) - Thornburg, Nicholas E.; Liu, Yangyang; Li, Peng; Hupp, Joseph T.; Farha, Omar K.; Notestein, Justin M.
Abstract : Zirconium(iv )-containing metal–organic framework (MOF) catalysts NU-1000 and MOF-808 were compared to analogous catalysts synthesized by grafting the nodes onto bare and functionalized silica. Abstract : Zirconium(iv )-containing metal–organic framework (MOF) catalysts NU-1000 and MOF-808 were compared to analogous catalysts synthesized by grafting the nodes onto bare and functionalized silica. As-synthesized, calcined, and activated catalysts all exhibit similar selectivity in the ring-opening of 1, 2-epoxyoctane with isopropanol, but MOF-808 gives exceptionally high rates and yields per gram catalyst.